Autoregressive Lag—Order Selection Using Conditional Saddlepoint Approximations - Ronald W. Butler; Marc S. Paolella (Econometrics, 2017)
A new method for determining the lag order of the autoregressive polynomial in regression models with autocorrelated normal disturbances is proposed. It is based on a sequential testing procedure using conditional saddlepoint approximations and permits the desire for parsimony to be explicitly incorporated, unlike penalty-based model selection methods. Extensive simulation results indicate that the new method is usually competitive with, and often better than, common model selection methods.